2000
DOI: 10.1021/ol000046x
|View full text |Cite
|
Sign up to set email alerts
|

Titanium(IV) Chloride and the Amine-Promoted Baylis−Hillman Reaction

Abstract: In the Baylis-Hillman reaction, we found that, when the reactions of arylaldehydes with methyl vinyl ketone were carried out at <-20 degrees C using a catalytic amount of amine as a Lewis base in the presence of titanium(IV) chloride, the chlorinated compounds 1 could be obtained as the major product in very high yields for various arylaldehydes. In addition, acrylonitrile could undergo the same reaction to give the corresponding chlorinated product in moderate yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Among those Lewis acids examined, TiCl 4 has been successfully used to promote the Baylis-Hillman reaction in the presence of Lewis base catalysts [ 9 , 11 , 12 ]. During our own investigations of the Baylis-Hillman process we found that many amines are very effective Lewis bases in this interesting reaction and the reaction products differ considerably from those reported so far [ 13 ]. Herein we wish to report the full details of the titanium (IV) chloride, boron (III) chloride or zirconium (IV) chloride and amine promoted Baylis-Hillman reactions, along with a plausible reaction mechanism based on the previous findings and our own results.…”
Section: Introductionmentioning
confidence: 76%
“…Among those Lewis acids examined, TiCl 4 has been successfully used to promote the Baylis-Hillman reaction in the presence of Lewis base catalysts [ 9 , 11 , 12 ]. During our own investigations of the Baylis-Hillman process we found that many amines are very effective Lewis bases in this interesting reaction and the reaction products differ considerably from those reported so far [ 13 ]. Herein we wish to report the full details of the titanium (IV) chloride, boron (III) chloride or zirconium (IV) chloride and amine promoted Baylis-Hillman reactions, along with a plausible reaction mechanism based on the previous findings and our own results.…”
Section: Introductionmentioning
confidence: 76%
“…Treatment of 4 a -c and 5 a -c with titanium(IV) chloride in refluxing chloroform for 1 hour caused intramolecular cyclocondensation to afford the corresponding tetrahydrothieno[2,3-b]pyridines 6a-c and 7a-c. Interestingly, we found the milder condition under which compounds 6a-c and 7a-c could be obtained in the presence of titanium(IV) chloride and triethylamine ( Table 2). Several investigators have reported an efficient transformation and cyclization by the action of a titanium(IV) chloride-amine combination [32][33][34][35]. In our reaction, it seems likely that since the rate of intramolecular cyclocondensation of 4 and 5 could be promoted by using triethylamine as the base at low temperature, 6a-c and 7a were obtained in somewhat better yields of 51, 44, 60 and 75%, respectively (entries 2, 4, 6 and 8).…”
Section: Pyridinesmentioning
confidence: 81%
“…Acrylates are normally very unreactive in Lewis acid catalyzed BH reactions, and very low to zero yields of coupling products are obtained 6b. 7c,7d Interestingly, our new methodology works very well for both electron‐poor and electron‐rich aromatic aldehydes, giving excellent yields of Baylis–Hillman products in only 10 min (entries 3–7). When acrylonitrile was employed, reactions with aromatic aldehydes also gave high product yields (entries 8 and 9).…”
Section: Baylis–hillman Reactions Of Aldehydes With Cyclic Enones Catmentioning
confidence: 92%